FIRST RECORD OF CHELONIBIA CARETTA (CIRRIPEDIA) ON Eretmochelys imbricata (TESTUDINES), IN BRAZILIAN LITTORAL - Chaves, L. S.; Farrapeira, C. M. R.; Guimarães, E. S.; Moura, G. J. B. (Revista Nordestina de Zoologia, 2014)
During the nesting season of 2008 – 2009, nine specimens of the barnacle Chelonibia caretta were found attached to the carapace of a female hawksbill turtle Eretmochelys imbricata in Porto de Galinhas Beach, northeast of Brazil. The present contribution reports for the first time this association in the Brazilian littoral, being the fourth occurrence of the turtle barnacle in this country. This rare occurrence of C. caretta in Brazilian coast and its known connection with the turtle Caretta caretta as its main host, brings evidence on this record’s importance as it provides data for inferences about the feeding habits and migration of the E. imbricata in the South Atlantic.